2023
DOI: 10.1088/1755-1315/1210/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic waste collection system - A proposed innovation for Indian Institute of Technology, Roorkee Campus, India

Abstract: Solid Waste Management (SWM) is a challenging issue to be addressed in most of the urban centres in India. Heavy population densities and exponential growth of the cities’ boundaries, due to migration, create kiosks to the cities’ resources such as land and other amenities. In such cities, the unsegregated waste gets generated in huge quantities while the rest are dumped in landfill sites without any specific treatment. Centralised and holistic approaches are missing, as most of the waste-to-energy & waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…To investigate the triaxial mechanical properties of TIR, Kumar [46] found that the triaxial compressive strength under different confining pressures shows a trend of first decreasing and then increasing with an increasing bedding angle, which is consistent with the changing trend of the UCS with the bedding angle (Figure 9a). Singh et al [85] noticed that the variation in strength under different bedding angles increases with the confining pressure according to the data of Kumar [46], and the behavior is observed to be nonlinear, as shown in Figure 9b. For transversely isotropic rocks, this conclusion has been confirmed in the literature [86][87][88][89][90][91][92].…”
Section: Mechanical Properties and Strength Criteria Under Triaxial C...supporting
confidence: 66%
See 3 more Smart Citations
“…To investigate the triaxial mechanical properties of TIR, Kumar [46] found that the triaxial compressive strength under different confining pressures shows a trend of first decreasing and then increasing with an increasing bedding angle, which is consistent with the changing trend of the UCS with the bedding angle (Figure 9a). Singh et al [85] noticed that the variation in strength under different bedding angles increases with the confining pressure according to the data of Kumar [46], and the behavior is observed to be nonlinear, as shown in Figure 9b. For transversely isotropic rocks, this conclusion has been confirmed in the literature [86][87][88][89][90][91][92].…”
Section: Mechanical Properties and Strength Criteria Under Triaxial C...supporting
confidence: 66%
“…More experimental studies are needed to further verify this. [50][51][52][53][54], (c) shale [35,52,53,[55][56][57][58], (d) sandstone [53,[59][60][61][62], (e) slate [46,63,64], (f) gneiss [52,65], limestone [53], orthoquartzie [46], travertine [49], and siltstone [59]. [53,[59][60][61][62], (e) slate [46,63,64], (f) gneiss [52,65], limestone [53], orthoquartzie [46], travertine [49], and siltstone [59].…”
Section: Mechanical Properties and Failure Characteristics Under Unia...mentioning
confidence: 99%
See 2 more Smart Citations